STRATEGY OF POKMASWAS TELUK SAMUDERA IN MARINE AND FISHERIES RESOURCES MANAGEMENT SASAK KANAGARIAN COASTAL LAND SASAK RANAH PASISIE DISTRICT PASAMAN BARAT CITY WEST SUMATRA PROVINCE - Rahma Febri; Ridar Hendri; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on 1st June to 11st July, 2015. The purpose of this study was to identify potential, review management strategies that are run, and formulated alternatif strategy for Pokmaswas Teluk Samudera strategy. The method used was case study metod. The infrmans was choosen with purposive sampling. The informans in this study comprising of 4 people consisting of Chairman Pokmaswas Teluk Samudera, Wali Nagari Sasak, head of UNIT PPI Sasak, head of KP3K in marine and fisheries departement of west Pasaman.The results of this research showed that the Pokmaswas Teluk Samudera was concern to managing the potential of fish catching, fish processing, marketing of fisheries, marine tourism, mangrove forests, and human resources. Pokmaswas Teluk Samudera formed on 2013 and completed some activities in marine and fisheries resource management on the coast of Sasak. To support their existance, need to formulated alternative management strategies by using the SWOT analysis to determine the strengths, weaknesses, opportunities, and threats of internal and external factors the Group. Each factor was scored according to their importance. The final step was selected the best alternatives strategic for Pokmaswas Teluk Samudera. It can be recommended as many as 3 alternative strategies : to creat the local regulations was scored about 3,72 points, to plan meeting consistantly was scored about 3,27 points, to standarize funding sources from govermant and personal groups was scored about 3,26 points.Key words: Pokmaswas, Marine and fisheries Potential, alternative strategies,